Mathematics learning skills and thinking development (Journal of Parents and Teachers, 2024)
The creative search for solutions and the abstraction of concepts are key themes, highlighting the importance of understanding mathematical principles to perform exercises. The linking of concepts and the application of rules and sequences in learning are emphasized. Challenges in the creation of innovative solutions are also identified, suggesting the evaluation of trends and related topics to enrich the educational process.
Keywords: solutions; concepts; application; innovation